Subpleural emphysema as a rare initial manifestation of an iatrogenic tracheal penetration: a case report - Minori Nakamura; Shuhei Iizuka; Toru Nakamura (Surgical Case Reports, 2022)
Abstract Background Iatrogenic tracheal injury is a rare but potentially morbid condition and often poses a diagnostic challenge due to its rarity and the lack of specific clinical findings. Because a delayed diagnosis is associated with a higher mortality, a prompt diagnosis is essential. We report a case of an iatrogenic tracheal injury detected by subpleural emphysema as a rare initial manifestation. Case presentation A 75-year-old woman was diagnosed with stage IA2 right lung cancer. During the surgery, visceral subpleural emphysema developed along the lung surface up to the interlobar fissure followed by subcutaneous emphysema in the anterior neck. Suspecting a tracheal injury, we aborted the surgery. Fiberoptic bronchoscopy revealed a longitudinal laceration on the membranous part of the distal trachea without esophageal involvement, consistent with a level II injury. Conservative management was chosen and she had a successful recovery. Conclusions Iatrogenic tracheal injury could initially manifest as visceral subpleural emphysema. Once subpleural emphysema is observed during surgery, a prompt diagnostic workup of the tracheal injury should be performed.